Structure and expression of Rhodnius prolixus GH18 chitinases and chitinase-like proteins: Characterization of the physiological role of RpCht7, a gene from subgroup VIII, in vector fitness and reproduction - Gama, Maiara do Valle Faria; Moraes, Caroline Silva; Gomes, Bruno; Diaz-Albiter, Hector Manuel; Mesquita, Rafael Dias; Seabra-Junior, Eloy; Azambuja, Patrícia; Garcia, Eloi de Souza; Genta, Fernando Ariel (Frontiers in Physiology, 2022)
Chitinases are enzymes responsible for the hydrolysis of glycosidic linkages within chitin chains. In insects, chitinases are typically members of the multigenic glycoside hydrolase family 18 (GH18). They participate in the relocation of chitin during development and molt, digestion in detritivores and predators insects, and control the peritrophic membrane thickness. Chitin metabolism is a promising target for developing new strategies for vector control, and knowledge of the roles of chitinases may reveal new targets and bring light to unique aspects of their physiology and interaction with microorganisms. Rhodnius prolixus is an important vector of Chagas disease caused by the parasite Trypanosoma cruzi. In this study, we performed annotating and structural characterization of nine chitinase and chitinase-like protein genes in the R. prolixus genome. The role of their corresponding transcripts was studied in more depth, and their physiological role was studied through silencing by RNAi. Phylogenetic analysis of coding sequences showed that these genes belong to different subfamilies of GH18 chitinases already described in other insects. The pattern of expression of these genes in different tissues and developmental stages was initially characterized using RT-PCR. RNAi screening showed silencing of the gene family members with very different efficiencies. Based on the knockdown results and the general lack of information about the subgroup VIII of GH18, the RpCht7 gene was chosen for phenotype analysis. RpCht7 knockdown doubled the mortality in starving fifth instar nymphs compared to dsGFP injected controls. However, it does not alter blood intake, diuresis, digestion, molting rate, molting defects, sexual ratio, percentage of hatching, and average hatching time. Nevertheless, female oviposition was reduced by 53% in RpCht7 silenced insects, and differences in oviposition occurred within 14 to 20 days after a saturating blood meal. These results suggest that RpCht7 may be involved in R. prolixus reproductive physiology and vector fitness.